2004
DOI: 10.1039/b309804d
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of textured thermoelectric layered cobaltites with various rock salt-type layers by using β-Co(OH)2platelets as reactive templates

Abstract: Textured bulk ceramics have been prepared of various cobaltites including the common CdI 2 -type CoO 2 layer (i.e., [Ca 2 (Co 0.65 Cu 0.35 ) 2 O 4 ] 0.624 [CoO 2 ]: CCO-4-layer, [Bi 2 M 22x O 4 ] p [CoO 2 ] (M 2 ~Sr 2 : BSCO, M 2 ~Ca 1 Sr 1 : B(SC)CO, M 2 ~Ca 2 : BCCO)) by using b-Co(OH) 2 (CdI 2 -type) platelets as reactive templates, and their thermoelectric (TE) properties have been examined. All the specimens were found to be highly c-axis aligned ceramics. Especially for CCO-4-layer, B(SC)CO and BCCO, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
111
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 21 publications
15
111
6
Order By: Relevance
“…This evolution of the resistivity values is consistent with the reduction of the amount of the secondary phases observed in the SEM images and also with the apparent density values for all the samples. Furthermore, for samples obtained by the polymer solution method, ρ is nearly temperature independent and it is close to the values obtained for textured materials (~ 15 mW.cm at 275 ºC) [7] or single crystals (~ 18 mW.cm at room temperature) [14]. (125 mV/K at 275 ºC) [7] or single crystals (110 mV/K at room temperature) [14].…”
Section: Sintered Materials Characterizationsupporting
confidence: 49%
See 1 more Smart Citation
“…This evolution of the resistivity values is consistent with the reduction of the amount of the secondary phases observed in the SEM images and also with the apparent density values for all the samples. Furthermore, for samples obtained by the polymer solution method, ρ is nearly temperature independent and it is close to the values obtained for textured materials (~ 15 mW.cm at 275 ºC) [7] or single crystals (~ 18 mW.cm at room temperature) [14]. (125 mV/K at 275 ºC) [7] or single crystals (110 mV/K at room temperature) [14].…”
Section: Sintered Materials Characterizationsupporting
confidence: 49%
“…Crystallographically, these cobaltites are composed of two different layers, with an alternate stacking of a common conductive CdI 2 -type CoO 2 layer, with a two-dimensional triangular lattice, and an insulating block layer, with the rocksalt-type (RS) structure. The two sublattices (RS block and CdI 2 -type CoO 2 layer) possess common a-and c-axis lattice parameters and b angles but different b-axis length, causing a misfit along the b-direction [6][7][8] that gives their common name: misfit cobaltites.…”
Section: Introductionmentioning
confidence: 99%
“…This misfit system exhibits a large thermopower TEP 300 ~150 µV/K and a rather low resistivity value [5][6][7]. Due to its high structural anisotropy, the alignment of plate-like grains by mechanical and/or chemical processes is necessary to attain macroscopic properties comparable to the intrinsic crystallographic ones.…”
Section: Introductionmentioning
confidence: 99%
“…These layers show an alternate stacking of a common conductive CdI 2 -type hexagonal CoO 2 layer with a two-dimensional triangular lattice and a block layer composed of insulating rock-salt-type (RS) layers. The two sublattices (RS block and CdI 2 -type CoO 2 layer) possess common a-and c-axis lattice parameters and β angles, but different b-axis length, causing a misfit along the b-direction [10,11]. Furthermore, it has also been found that the Seebeck coefficient values are governed by the incommensurability ratio and/or the charge of the RS block layer between the CoO 2 ones [9].…”
Section: Introductionmentioning
confidence: 99%